Unbelievers Mental Model And Behavioural Disorders Based On Their Queries In The Albaqarah Chapter - Muhammad Widus Sempo; Norita Binti Md Norwawi; Hasyim Haddade; Yousuf Mahbubul Islam; Noorhayati Binti Hasyim (Fakultas Adab & Humaniora UIN Alauddin, 2024)
Jurnal Adabiyah Vol 20. No 2/2020